Rare mandibular metastasis of neuroblastoma in a child: a case report - Safaa El Omari; Malika Afif; Sana Bensouda; Samira El Arabi (Frontiers in Dental Medicine, 2026)
Although neuroblastoma is a common malignant tumor in children and distant metastases are frequently observed, involvement of the mandible remains rare. We report the case of a 7-year-old boy presenting with a right mandibular mass associated with an oral lesion in the region of tooth 46, suggestive of a secondary lesion. Histopathological examination of the biopsy specimen confirmed the diagnosis, whereas imaging initially suggested lymphoma, soft tissue sarcoma, or osteosarcoma. Staging work-up revealed an adrenal neuroblastoma with multiple bone metastases. Given the extent of tumor involvement and the advanced stage of the disease, palliative chemotherapy was initiated. The clinical course was unfavorable, marked by the development of additional disseminated metastases, leading to the patient's death 14 months after the diagnosis of mandibular metastasis. This case highlights the importance of early multidisciplinary collaboration between pediatric dentistry and pediatric oncology teams to optimize diagnostic and therapeutic management in such patients.